Hubungan Emosi Positif dan Koping dengan Hipertensi di RSUP. M. Djamil Padang : The Relationship of Positive Emotion and Coping with Hypertension in General Hospital. M. Djamil Padang - Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2012)
The number of visitations of patients who suffered from hypertension in Dr. M. Djamil Hospital increased by 914 in 2006 and 1892 in 2007. The aim of this study is to understand the correlation between emotional and coping tendencies with blood pressure. This correlation study was conducted with a sample of 86 individuals who had the ability to read and write in Padang city and were under the age of 60. The analysis used in this study was double correlation parameter analysis. The results of this data analysis showed significant correlations between positive emotion and proactive coping as control variables with systolic blood pressure and diastolic blood pressure. The significant coefficient test produced values of p = 0.002 and p = 0.025.